Early Functional and Cognitive Declines Measured by Auditory-Evoked Cortical Potentials in Mice With Alzheimer’s Disease - Mei, Ling; Liu, Li-Man; Chen, Kaitian; Zhao, Hong-Bo (Frontiers in Aging Neuroscience, 2021)
Alzheimer's disease (AD) is characterized with a progressive loss of memory and cognitive decline. However, assessment of AD-associated functional and cognitive changes is still a big challenge. Auditory evoked cortical potential (AECP) is an event-related potential reflecting not only neural activation in the auditory cortex but also cognitive activity in the brain. In this study, we used the subdermal needle electrodes with the same electrode setting as the auditory brainstem response (ABR) recording and recorded AECP in normal aging CBA/CaJ mice and APP/PS1 AD mice. AECP in mice usually appeared three positive peaks, i.e., P1, P2, and P3, and three corresponding negative peaks N1, N2, and N3. In normal aging CBA mice, the early sensory peaks P1, N1, and P2 were reduced as age increased, whereas the later cognitive peaks N2, P3, and N3 were increased or had no changes with aging. However, the latency of P1 peak was increased as age increased, although the latencies of later peaks had significant reduction with aging. In AD mice, peak P1 was significantly reduced in comparison with wild-type (WT) littermates at young ages, proceeding AD phenotype presentation. In particular, the later cognitive peak P3 was diminished after 3 months old, different from normal aging effect. The latencies of AECP peaks in AD mice generally had no significant delay. Finally, consistent with AECP changes, accumulation of amyloid precursor protein (APP) at the auditory cortex was visible in AD mice as early as 2 months old. These data suggest that AECP could serve as an early, noninvasive, and objective biomarker for detecting AD and AD-related dementia.